Mulheres que amam mulheres: direitos humanos, territórios e visibilidade - Marques, Louise Hermania de Oliveira (2021)
The networks of power and patriarchal domination despise non-heteronormative sexualities, dictate the social game and place lesbian women in spaces of exclusion, heightened when intersectionalized with categories such as race and class. This study asked how lesbian invisibility in public spaces affects the guarantee of Human Rights in this segment in Brazil. The general objective was to analyze the construct of lesbian invisibility from the articulation with the categories of culture and territory, seeking to understand the injunctions between these and human rights violations. We also sought to understand the intricacies of gender asymmetries in the systematic production of power and its relationship with the constitution of spaces, recording some actions of these women to break the cycle of social invisibility that surrounds them. Therefore, women activists from the Maria Quitéria Group of Lesbian and Bisexual Women, from João Pessoa-PB, were interviewed, and from the reports it was observed how they perceive the constitution of lesbian invisibility and what are the consequences of this in the access to public and human rights guarantees of this group. The methodology was characterized by interdisciplinarity, used the deductive method in the presentation of explanations based on theories of law, geography, anthropology, sociology, political science, culture, gender and sexuality, in the critique of heteronormative binarism to understand the experience of women lesbians. By presenting the “voices” directly affected by the Brazilian misogynist politics, the study brings visibility to the segment, giving space, authority and freedom so that their stories, with the most varied contexts and subjectivities, are heard and academically positive. The study can state that lesbian women occupy the space of non-existence, a territory not demarcated by male domination, and when they recognize each other, they declare themselves socially and politically, they begin to mark their territory: the territory of resistance.